THE EFFECTIVENESS OF USING BERLITZ METHOD IN TEACHING VOCABULARY ON TENTH GRADE OF SMA PGRI SUNGGUMINASA - Singgi Sahid Kurniawan; Yusniati N. Sabata (English Education Study Program, 2022)
This research aimed to find out the effectiveness of using Berlitz method in teaching vocabulary in terms of noun and verb at first year of SMA PGRI Sungguminasa. The researcher applied experimental method with one group pretest-posttest design. One group was pretested (O1), exposed to a treatment (X) and post-tested (O2). The researcher conducted the treatment in six times meetings. It employed vocabulary test as instrument. The subject of the research were 21 students in XIPS class.The result of statistical analysis of t-test with degree of freedom (df) = n-1, where n=21, (df=20) at the level of significance 0.05 indicated that there was a significance differences between the mean score of the post-test and pre-test. The mean score of pre-test was 30.53 and the mean score of post-test was 56.36. thus, the null hypothesis (H0) was rejected, while alternative hypothesis (H1) was accepted. Therefore, the hypothesis of the research states that There is a significant difference between the students’ vocabulary mastery after using Berlitz method at the first grade of SMA PGRI Sungguminasa in academic year 0f 2014.